An analysis of security challenges and their perspective solutions for cloud computing and IoT - Muhammad Muhammad; Tahir Alyas; Faraz Ahmad; Fatima Butt; Wajahat Qazi; Shazia Saqib (EAI Endorsed Transactions on Scalable Information Systems, 2021)
INTRODUCTION: With the on-going revolution inthe Internet of Things and Cloud Computing has made the potential of every object that is connected through the Internet, to exchange and transfer data. Various users perceive this connection and interaction very helpful and serviceable in their daily routines. OBJECTIVES: The objective of this research to identify the complex configured network system is a soft target to security threats, therefore we need a security embedded framework for IoT and cloud communication models. Another objective is to provide protection of information from unauthorized access controls in IoT-cloud integrated framework and secure data from spying. METHODS: This paper has applied an integrated IoT-cloud theoretical solution, whose activities are mainly decided by a centralized controller to provide safeguard against data attacks. Our theoretical integrated IoT-cloud theoretical solution is able to achieve unauthorized access control and data breach. RESULTS: Internet of things and cloud computing has intensively used by several real-time applications. After the thercical analysis, the different vulnerabilities explained after detail literature review to prevent unauthorized access and unauthorized data breach. CONCLUSION: Internet of things have changed the shape of communicationand centralized data controller is the main entity that is robust against eavesdroppers. In case, any eavesdropper tries to be a normal user and attempts to access a personal file then he has been entertained with a misleading file that he considers as an authentic file but in actual it is not. Desirable IoT proposed solutions need to be design and deploy, which can guarantee: anonymity, confidentiality, andintegrity in heterogeneous environments.